PRODUCTIVE ASSESSMENT AND QUALITY OF GRAIN IN FIVE HYBRID OF MAIZE (Zea mays L.) IN TWO LOCATIONS FROM LOS RIOS PROVINCE - Díaz Coronel, Teofilo Gorki (2009)
The research was conducted during the rainy season, at the Universidad Tecnica Estatal de Quevedo and the Instituto Tecnologico Agropecuario de Vinces. The objective was to determine the performance of five maize hybrids adapted to the soil and climatic conditions of the Guayas River basin, based on production and protein quality of seeds. A Complete Randomized Block Design was used along with five treatments (hybrids: INIAP H-551, INIAP H-552, R-8330 Winner, 8501 and Dekalb Brasilia 5005) and four replications, considering individual and combined analysis. For means comparisons Tukey test at 5% probability was used. There was a higher yield per hectare in the Vinces locality (P≤0.05), this is attributed to the increased length, number of rows and weight of grains per ear. In relation to the nutritional quality of grain it was determined that the performance of the hybrids ‘Dekalb 5005’ and ‘Winner R-8330 was inversely proportional to the quality of the protein, due to a low content of lysine.